«The life of st. John Chysostom» by George of Alexandria - Balakhovskaia Aleksandra (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2012)
«The Life of St. John Chrysostom» was written in the second part of the 7th century by an unknown author and inscribed with the name of George, the bishop of Alexandria. It is a compilation of diff erent sources, including folk legends about the saint, which were very popular among medieval readers. But the information from these sources requires critical approach, because they often distort the real historical image of St. John Chrysostom.